The chicken doesn't skate eaudiobook - Korman, Gordon (Recorded Books Inc., 1999)
Sixth-grader Milo Neal plans to do a science project on "The Complete Life Cycle of a Link in the Food Chain." But when he brings his specimen-a baby chick-to class, everyone falls in love with the cute ball of fluff. Soon she has a name: Henrietta. Not only is Henrietta the class pet, she's even chosen as mascot for the school hockey team! How can Milo finish his project, which calls for frying up his specimen and serving it to the judges of the science fair? Each day, as Henrietta gets bigger, so does Milo's dilemma. And students are hatching plans to rescue their feathered friend. Gordon Korman, author of more than 20 books for middle school and young adult audiences, based this hilarious story on his own experiences while visiting a middle school classroom. Through the talented narrators' performances, Henrietta's adventures will have you cackling with laughter.